Developing a Standardized Elementary Teacher Teaching Competence Self-assessment Tool - Hung, Le Thai; Bich, Nguyen Thi; Sinh, Cao Thi (VNU Journal of Science: Education Research; Vol 36 No 3DO - 10.25073/2588-1159/vnuer.4446, 2020)
This paper aims to develop a standardized self-assessment tool to assess elementary teachers' teaching competence. The paper surveyed 375 elementary school teachers and the survey results show that the developed toolkit was highly reliable with Cronbach's Alpha Coefficient > 0.7. Among the five identified competencies, the professional development competence in response to the new general education curriculum was self-assessed at the lowest level by the teachers (mean = 2.5/4, SD = 0.5). The standardized toolkit is expected to help elementary school teachers self-assess and improve their skills to meet the required standards.